2014
DOI: 10.5935/abc.20140052
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fibrosis and Ventricular Arrhythmias in Chagas Heart Disease Without Ventricular Dysfunction

Abstract: BackgroundPatients with Chagas disease and segmental wall motion abnormality (SWMA) have worse prognosis independent of left ventricular ejection fraction (LVEF). Cardiac magnetic resonance (CMR) is currently the best method to detect SWMA and to assess fibrosis.ObjectiveTo quantify fibrosis by using late gadolinium enhancement CMR in patients with Chagas disease and preserved or minimally impaired ventricular function (> 45%), and to detect patterns of dependence between fibrosis, SWMA and LVEF in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 20 publications
1
33
1
10
Order By: Relevance
“…The percentage of patients with LE was higher in our study (87% vs 68.6% in the Rochitte study). The difference was mainly in the indeterminate group, where we found LE in 50% compared with 20% of Rochitte and 19.2% reported by Tassi et al This difference could be due to different stages of the disease, as well as differences in the software used in the image analysis. It is possible that the patients that were classified as indeterminate (by clinical, ECG and echocardiogram) but with LE in the MRI in the present paper could be reclassified as CC in the future.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The percentage of patients with LE was higher in our study (87% vs 68.6% in the Rochitte study). The difference was mainly in the indeterminate group, where we found LE in 50% compared with 20% of Rochitte and 19.2% reported by Tassi et al This difference could be due to different stages of the disease, as well as differences in the software used in the image analysis. It is possible that the patients that were classified as indeterminate (by clinical, ECG and echocardiogram) but with LE in the MRI in the present paper could be reclassified as CC in the future.…”
Section: Discussioncontrasting
confidence: 56%
“…Rochitte et al found that in CC patients, the myocardial segments that had LE more frequently were the inferior and inferolateral basal and mid, whereas Tassi et al and Regueiro et al found that the inferolateral basal and mid segments were the most frequently involved. The relationship between the distribution of LE and the presence of VT was not evaluated in none of these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 During the acute phase, the inflammatory response is designed to eliminate parasites whereas during the chronic phase, it is rather controlled in such a way that the immune response is targeted to maintain the parasite at check preventing excessive tissue damage, fibrosis formation, and cardiac loss of function. [2][3][4] Since the presence of T. cruzi is the switch for inducing and maintaining the inflammatory process running in the heart tissue, three cardinal therapeutic strategies are proposed: 1) an antiparasitic drug, where benznidazole is considered a standard treatment but still ineffective to those symptomatic individuals in chronic stage of Chagas cardiopathy 5 ; 2) drugs that act direct on the cardiac dysfunction avoiding progressive failure of the organ-for example, diuretics, digitals, β-blockers, and angiotensin-converting enzyme (ACE) inhibitors 6,7 and, more recently, 3) drugs that act in controlling the over-reactivity of the immune system avoiding severe destruction in the heart during chronic stage of the infection-for example, statins and ACE inhibitors. [8][9][10][11][12] ACE inhibitors have been shown to be efficacious not only as therapies against hypertension and protection against left ventricular hypertrophy but also in the regulation of the immune system related to distinct diseases, including the T. cruziinduced pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia‐Alvarez et al have also reported early diastolic dysfunction associated with worsening contractile function, and decreased untwisting velocity, contributing to ventricular dysfunction. Tassi et al suggested that endomyocardial fibrosis can be present in initial ChD stages in patients without systolic dysfunction; additionally, ChD patients with segmental wall‐motion abnormalities and preserved LVEF have a worse prognosis . Regional GLS alteration supports the pathophysiological hypothesis of a predominant focal endomyocardial fibrosis as an inherent feature of ChD leading to aneurysmatic remodeling of basal segments of the inferolateral, lateral, and all apical segments …”
Section: Discussionmentioning
confidence: 94%